Case report: Acute pericarditis following hepatic microwave ablation for liver metastasis - Pavon, Anna Giulia; Rubimbura, Vladimir; Nowacka, Anna; Hocquelet, Arnaud; Schwitter, Jurg; Rotzinger, David C. (Frontiers in Cardiovascular Medicine, 2023)
Hepatic microwave ablation (MWA) is a growing treatement in the fied of metastatic liver tumors. However the potential risk is to damage the adjacent structures if the hepatic lesion is near the diaphragm. Even if it is a rare complication, hemorrhagic cardiac tamponade is a life-theraten complication already described in this situation. Herby we present the case of a 55-year old man presented with late cardiac tamponade following MWA treatment. Adequate timely management is important and clinicians should be fully aware of performing transthoracic echocardiography to early detect sign of pericardial effusion in any case of suspicion of cardiac involvement.Potential cardiovascular complications are possible after MWA for liver tumors located at segment II. Even if cardiac tamponade has always been decribed as an immediate complication, it can also appear later on due to acute pericarditis following the heat tissue damage.